Ternary Artificial Nacre Reinforced by Ultrathin Amorphous Alumina with Exceptional Mechanical Properties. Issue 10 (18th January 2016) - Zhao, Hewei; Yue, Yonghai; Zhang, Youwei; Li, Lidong; Guo, Lin
Abstract : A novel ternary artificial nacre is developed through a vacuum‐assisted filtration method, with reinforced ultrathin amorphous alumina that is grown in situ on the surface of GO. This ternary artificial nacre simultaneously shows exceptional strength and toughness, which have, up to now, been considered to be mutually exclusive. This novel material will play a role in the structuring of future materials.